The Relationship Between Self-Concept and the Tendency of the Cinderella Complex Among Female Students Living Away from Home in Banda Aceh - Afrila, Siti Widya; Safrilsyah, Safrilsyah; Ridha, Usfur; Zainuddin, Muslim (Fathana, 2023)
The Cinderella Complex is a network of attitudes and fears, most of which are repressed, that prevent women from fully utilizing their intellectual abilities and creativity. This study aims to examine the relationship between self-concept and the tendency of the Cinderella Complex among female students living away from home in Banda Aceh. This research employed a quantitative approach using a correlational method. The measurement instruments used were the Self-Concept Scale, developed by the researcher based on the aspects proposed by Calhoun and Acocella (1990), and the Cinderella Complex Scale, which was constructed based on the aspects suggested by Dowling (1995). The study involved 200 female students who were living independently in Banda Aceh. The sampling method used was non-probability sampling with the purposive sampling technique. Hypothesis testing was conducted using the Spearman correlation test. The results showed a correlation coefficient of r = -0.426 with a significance value (ρ) = 0.000, indicating a highly significant negative relationship between self-concept and the tendency of the Cinderella Complex. This means that the higher the level of self-concept, the lower the tendency toward the Cinderella Complex; conversely, the lower the self-concept, the higher the tendency toward the Cinderella Complex among female students living away from home in Banda Aceh.